Effects of Tea Consumption on Risk of Osteoporotic Bone Fracture in Older People: Meta-Analysis of Observational studies - Ehsan Modirian; Robab Sahaf; Ahmad Ali Akbari Kamrani; Mahshid Foroughan; Maryam Zarif Yeganeh; Fatemeh Shoaei; Hamed Basir Ghafouri; Fariba Kolahdouz (University of Social Welfare & Rehabilitation Sciences, 2011)
Objectives: There have been several studies published in the medical literature over the past 30 years that address the association between tea consumption and osteoporosis with inconsistent findings. A meta-analysis was undertaken, including 8 studies, to determine the effect of tea consumption on the risk of fracture. Methods & Materials: This systematic review and meta-analysis conducted on articles published from 1980 to 2010. We searched the following electronic databases: medline, pubmed, ISI, Embase and Chocrane and also reverent journals using mesh search terms including caffeine, tea, coffee, osteoporosis, Bone Mineral Density (BMD) and fracture*. All the relevant English written articles reviewed by two independent researchers. After title and abstract review non-relevant articles were excluded. The full text of accepted publications was obtained and their content reviewed for final inclusion. Using MOOSE (Meta-analysis Of Observational Studies in Epidemiology) criteria, relevant articles with high quality, reporting odds ratio (OR) or risk ratio (RR) for fracture following tea consumption, selected for meta-analysis. Results: Four hundred and twenty one articles found through the primary searches 78 full text articles evaluated. Only 8 of them fulfilled all the inclusion criteria and their relevant data were extracted included into the analysis. The meta-analysis showed that tea consumption can have a protective effect on the risk of hip fracture which is not significant (RR=0.872, 0.733-1.038). Analysis by type of the studies suggests that according to cohort studies there is a significant decrease in the risk of hip fracture following tea consumption (RR=0.749, 0.603-0.929) while case-control studies do not support this findings (RR=1.157, 0.863-1.553). Conclusion: Tea as a popular drink throughout the world can reduce the risk of osteoporotic bone fractures along with its known antioxidant effects.